The Iconography of the Coronation of the Virgin in Late Medieval Italian Painting: A Case Study - Salvador González, José María (Eikón / Imago, 2013)
This paper aims to highlight the artistic and conceptual relevance acquired by the iconographic theme of The Coronation of the Virgin in Italy during the Late Middle Ages. To achieve this goal we analyzed twenty-seven Trecento and Quattrocento paintings, with the purpose of discovering in them the more or less innovative compositional formulas proposed by these artists, as well as the possible literary sources that inspired them. From the formal perspective we have discovered three different iconographic types, which complement themselves mutually, as progressively complex variations of a similar basic structure. From the conceptual perspective we could also specify that these three different iconographic types of The Coronation of the Virgin in Italy are inspired directly in specific comments by some Church Fathers and medieval theologians.